Precocious Puberty: A Case Report - Munmun, Salma Akter; Chowdhury, Shiuly; Nasrin, Begum; Ara, Rowson; Parvin, Nahida (Ibrahim Cardiac Medical Journal, 2015)
A 4 years old girl was brought to the Department of Obstetrics and Gynaecology (of Bangabandhu Sheikh Mujib Medical University) for cyclical pervaginal bleeding and breast development. Her medical and family history was unremarkable. Evaluating her clinical presentations and investigations she was diagnosed as a case of precocious puberty. This case report emphasized how this condition should be evaluated and how these cases are to be managed. Ibrahim Cardiac Med J 2014; 4(1): 38-41